Corporate Governance, Commitment to Business Ethics, and Firm Valuation: Evidence from the Korean Stock Market - Pae, Jinhan; Choi, Tae Hee (2011)
A variety of stakeholders have long been interested in the factors that are related to firm valuation. This article investigates why companies with more comprehensive corporate governance (CG) have a value premium over companies with less comprehensive CG. We posit and find that the cost of equity capital (COC) decreases with the strength of CG, suggesting that the value premium stems from the lower COC for more comprehensive CG. We also find that the COC is lower for companies with strong commitment to business ethics (BE) than for those with weak commitment to BE and that the beneficial effect of CG on the COC is more pronounced for companies with weak commitment to BE than for those with strong commitment to BE. Companies with more comprehensive CG tend to exhibit strong commitment to BE, but the beneficial effect of corporate ethical commitment is not completely subsumed by CG. Our results suggest that companies could lower their cost of equity capital and increase firm value by adopting more comprehensive CG practices and committing to higher standards of BE.
Keywords: Valuation; cost of capital; Corporate Governance; Business Ethics; analysts’ forecasts